Interfaces do diálogo entre Paul Ricoeur e Claude Lévi-Strauss - Loschi, Geison Amadeu (2015)
This paper comes about as an outcome of an analysis of the works of Paul Ricoeur, which are at the starting point of insertion of hermeneutics in his philosophy. It was an attempt to follow the steps of formation of his concept of symbol, which is central to that period. Decisive for this phase, also called philosophy of symbol, was to put forward the question to other disciplines that played an essential role in the analysis of symbolic language, among which is the structural anthropology of Lévi-Strauss. Thus, the terms - more specific to the dialogue established between Paul Ricoeur and Claude Lévi-Strauss on the analysis of the symbolic language of myth - were defined. Finally, this research provides a better understanding of the opening phase of the Ricoeur s hermeneutics as well as its alignments and divergences with the structuralism of Lévi-Strauss so widespread in the academic field